2006
DOI: 10.1007/s11373-006-9081-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of total flavonoids from Laggera alata against carbon tetrachloride-induced injury in primary cultured neonatal rat hepatocytes and in rats with hepatic damage

Abstract: SummaryThe hepatoprotective activities of total flavonoids of Laggera alata (TFLA) were evaluated by carbon tetrachloride (CCl 4 )-induced injury in primary cultured neonatal rat hepatocytes and in rats with hepatic damage. In vitro, TFLA at a concentration range of 1-100 lg/ml improved cell viability and inhibited cellular leakage of two enzymes, hepatocyte aspartate aminotransferase (AST) and alanine aminotransferase (ALT), caused by CCl 4 . In vivo, oral treatment with TFLA at doses of 50, 100, and 200 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 28 publications
2
26
0
5
Order By: Relevance
“…At the same dose, D. edulis positively regulated glycaemia, restored the desirable lipids while not adversely affecting centres of metabolism and excretion, the liver and kidneys, as observed by the liver function markers, creatinine and urea results. Despite the diabetic state being associated with hepatocellular damage and leakages to cause a rise in liver marker levels such as AST, ALT and ALP, and also plant phytochemicals especially flavonoids associated with reversing such (Tapas et al 2008; Wu et al 2006), our experimental animal's liver enzymes were largely unchanged by the diabetic state. However, D. edulis extract was observed to reduce the ALT and ALP levels on day 15, similar to glibenclamide.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 82%
“…At the same dose, D. edulis positively regulated glycaemia, restored the desirable lipids while not adversely affecting centres of metabolism and excretion, the liver and kidneys, as observed by the liver function markers, creatinine and urea results. Despite the diabetic state being associated with hepatocellular damage and leakages to cause a rise in liver marker levels such as AST, ALT and ALP, and also plant phytochemicals especially flavonoids associated with reversing such (Tapas et al 2008; Wu et al 2006), our experimental animal's liver enzymes were largely unchanged by the diabetic state. However, D. edulis extract was observed to reduce the ALT and ALP levels on day 15, similar to glibenclamide.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 82%
“…Flavonoids improved cell viability and inhibited cellular leakage of hepatocyte AST and ALT (Su et al). Further, it is been shown that flavonoids can decrease the insulin resistance and insulin requirements in adipose and muscle tissue (Wu et al, 2006). Besides flavonoids, the plant contains alkaloid, glycosides, steroids and saponin that have hypolipidemic properties (Divya et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Bactericidal properties of the volatile oil are reported by Geda in 1995 [16]. Other species of Laggera such as L. pterodonta has been employed in herbal medicine in China as anti inflammatory agent for treatment of hepatitis, arthritis, bronchitis and nephritis [17][18]. However, no significant work has been reported on chemical composition and bioactivity related studies of the species found in Pakistan.…”
Section: Introductionmentioning
confidence: 99%